On the possibilities of using variants in Vulgata Bible for analysis of Church Slavonic biblical translations - Linek, Josef (Bohemica Olomucensia, 2013)
The treatise demonstrates the ways variants in the Vatican critical edition of the Vulgate can be used while analyzing Church Slavonic translations of biblical prophetic books (Prophetae minores) incorporated in Croatian Glagolitic breviaries.